Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1039/d0nr05132b
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of block copolymers for pore size control and reduced dispersity in mesoporous inorganic thin films

Abstract: Mesoporous inorganic thin films are promising materials architectures for a variety of applications, including sensing, catalysis, protective coatings, energy generation and storage. In many cases, precise control over a bicontinuous...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 67 publications
0
30
0
Order By: Relevance
“…[43] Please note that we did not observe changes in the Si-O stretching band at temperatures below 180 °C, which is typically referenced as suitable annealing temperature in literature. [18,44,45] In consequence, we did not apply intermediate annealing procedures but calcined the thin films directly after spin coating. FTIR measurements showed that the complete degradation of the PIB-b-PEO occurred between 240 °C to 270 °C in samples calcined in air, while the condensation of the inorganics started at 180 °C and continued up to 450 °C.…”
Section: Effect Of Temperature In the Fabrication Of Mesoporous Thin Films In Oxidizing And Inert Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…[43] Please note that we did not observe changes in the Si-O stretching band at temperatures below 180 °C, which is typically referenced as suitable annealing temperature in literature. [18,44,45] In consequence, we did not apply intermediate annealing procedures but calcined the thin films directly after spin coating. FTIR measurements showed that the complete degradation of the PIB-b-PEO occurred between 240 °C to 270 °C in samples calcined in air, while the condensation of the inorganics started at 180 °C and continued up to 450 °C.…”
Section: Effect Of Temperature In the Fabrication Of Mesoporous Thin Films In Oxidizing And Inert Conditionsmentioning
confidence: 99%
“…Hybrid thin films were fabricated following a protocol reported elsewhere. [17,18] In brief, a previously hydrolyzed aluminosilicate sol from aluminum-tri-sec-butoxide and (3glycidyloxypropyl)-trimethoxysilane (GLYMO) were mixed with the structure-directing agent PIB-b-PEO prior to thin film deposition by spin coating. The hybrid films were subsequently annealed in argon at a temperature of 450 °C.…”
Section: Two-step Calcination Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…37 A similar tendency was also observed for the synthesis of non-siliceous porous materials (e.g., carbon and titania) using PS-b-PEO. [38][39][40][41][42][43][44] In the case of the preparation of a mesoporous silica (SiO 2 ) film using PS-b-PEO, the resultant size of spherical pores was empirically explained by using PS and PEO lengths ( pore diameter ranging from 4 to 22 nm) 45 and PS/PEO ratios ( pore diameter less than 50 nm). 36 In the latter paper, large mesopores (∼40 nm) were very spherical but the diameter was not uniform and distributed in the range between about ±5 nm.…”
Section: Understanding the Formation Of Ps-b-peo Templated Poresmentioning
confidence: 99%
“…One approach introduced by our group is size exclusion chromatographic fractionation of polydisperse BCPs, which may serve for systematic pore size control and reduction of dispersity of the resulting mesoporous inorganic thin film architectures. [28] Alternative methods based on pore expansion by supramolecular co-assembly of swelling agents, carefully chosen to selectively interact with the pore-forming block, have been successfully implemented. To this end, benzene derivatives, [29,30] homopolymers, [31,32] carboxylic acids, [33,34] , or solvents such as toluene or xylene [35,36] have been used for tuning structural dimensions of the final inorganic mesoporous thin film.…”
Section: Introductionmentioning
confidence: 99%